Helping people help themselves : from the World Bank to an alternative philosophy of development assistance - Ellerman, David P. (Evolving values for a capitalist world., 2006)
Surveys the theoretical foundations for a philosophy of development - including the work of Albert Hirschman, Paolo Freire, John Dewey, and Soren Kierkegaard. The author offers a practical suggestion of how goals of development can be better set and met. He shifts the locus of initiative from the would-be helpers to the doers.